2019
DOI: 10.1093/jnci/djz152
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose and Volume to the Pancreas and Subsequent Risk of Diabetes Mellitus: A Report from the Childhood Cancer Survivor Study

Abstract: Background Childhood cancer survivors exposed to abdominal radiation (abdRT) are at increased risk for diabetes mellitus, but the association between risk and radiation dose and volume is unclear. Methods Participants included 20 762 5-year survivors of childhood cancer (4568 exposed to abdRT) and 4853 siblings. For abdRT, we estimated maximum dose to abdomen; mean doses for whole pancreas, pancreatic head, body, tail; and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 23 publications
1
43
1
Order By: Relevance
“…Also, HL patients required abdominal and cervical irradiation, yet we retrieved only TBI as a risk of hyperglycaemia development in our ALL cohort. Abdominal, cervical and cranial radiation did not appear to induce hyperglycaemia in our study, although this is contrary to findings in other studies which suggested the effect of abdominal radiation 30–32 . Strengths of our study include the large sample size of ALL patients, inclusion of risk factors for hyperglycaemia, complete patient records and numerous harmonized blood glucose data for ALL and NHL.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, HL patients required abdominal and cervical irradiation, yet we retrieved only TBI as a risk of hyperglycaemia development in our ALL cohort. Abdominal, cervical and cranial radiation did not appear to induce hyperglycaemia in our study, although this is contrary to findings in other studies which suggested the effect of abdominal radiation 30–32 . Strengths of our study include the large sample size of ALL patients, inclusion of risk factors for hyperglycaemia, complete patient records and numerous harmonized blood glucose data for ALL and NHL.…”
Section: Discussioncontrasting
confidence: 99%
“…RR leads to cancer relapse, poor treatment response, poor prognosis, decreased quality of life, and increased disease treatment burden. Furthermore, RR induces damage to canceradjacent normal tissues, disrupting the physiological and biochemical functions of normal tissue, resulting in symptoms, including radiation-related diarrhea, rectal bleeding, and radiation dermatitis [39][40][41] , as well as an increased risk of subsequent secondary cancer 26,[42][43][44] or chronic noncommunicable diseases including type II diabetes 45,46 or cardiovascular diseases 47 . Over the past century, to remove the barrier of RR, many studies have been carried out to investigate RR-related regulatory genes, molecules, and signaling pathways to uncover the underlying mechanisms of RR and to develop radiation sensitizers 48,49 .…”
Section: Introductionmentioning
confidence: 99%
“…Reduced secretion of insulin is probably related to the destruction of β-cells following radiation (9). By the antioxidant feature, AJ appears to decrease blood glucose levels, thus affecting pancreatic beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this pathologic condition, the occurrence of mutagenesis, altered number of Langerhans islets, and eventually, apoptosis are possible (8). In response to γ-ray exposure, diabetes occurs through impairment of insulin secretion (9). Recently, the mice exposed to a low dose of radiation (0.1 Gy) can disrupt the pancreatic cells (10).…”
Section: Introductionmentioning
confidence: 99%